Morphology-preserving smoothing on polygonized isosurfaces of inhomogeneous binary volumes. (January 2015) - Wei, Mingqiang; Zhu, Lei; Yu, Jinze; Wang, Jun; Pang, Wai-Man; Wu, Jianhuang; Qin, Jing; Heng, Pheng-Ann
Abstract: Polygonized isosurfaces of anatomical structures commonly suffer from severe artifacts (e.g., noise and staircases), due to inhomogeneous binary volumes. Most state-of-the-art techniques can reduce these artifacts but inevitably ruining anatomical structures' morphology. Given an initial polygonization of an isosurface, we first eliminate these apparent staircases based on a context-aware Laplace filter, and then solve the morphology-preserving problem of anatomical structures as an optimization of the local spatial quadrics (LSQ) of fitted Bézier surfaces during mesh evolution. This results in a conceptually simple approach that provides a unified framework for not only handling artifacts, but also for enabling the morphology preservation of anatomical structures. Highlights: We design an effective mesh smoothing framework that focuses on medical data. The LSQ gives an isosurface mesh a compact approximation to the underlying surface. We improve the staircase detection strategy by a novel cascaded operation.